Pengaruh Hafalan Al-Qur’an terhadap Prestasi Belajar Bahasa Arab Siswa - Aryati, Ani; Azizah, Nur; Hazmin, Hazmin (JOEAI (Journal of Education and Instruction), 2020)
The purpose of this study was to find out how to memorize the Al Qur'an students of SMK Muhammadiyah 2 Palembang, and to determine the effect of memorizing the Qur'an on learning achievement in Arabic. This type of research is field research (Field Research) using a quantitative approach. Data collection techniques using observation, questionnaires, interviews and documentation. The results of the study showed that the first, Al-Qur'an memorization of XII grade students of SMK Muhammadiyah 2 Palembang School, from the calculation of the average value of Variable X (Al-Qur'an Recitation) was 23.33 then it was included in the Very Good category. Secondly, the influence between memorization of Al-Qur'an with Arabic learning achievement from the calculation obtained by rxy Correlation Coefficient is 0.405 from the value of r table that is 0.330 at a significant level of 1% or 0.254 at a significant level of 5%, can be accepted and applied. Conclusion, memorization of Al-Qur'an The XII grade students of SMA Muhammadiyah 2 Palembang are included in the very good category and there is a very statistically significant effect on memorizing the Qur'an with the achievement of learning Arabic. Keywords: Arabic Language, Effect of Al-Qur'an Memorization, Learning Achievement